PERAN INTERNATIONAL JUSTICE MISSION (IJM) DALAM MENANGANI KASUS EKSPLOITASI ANAK SECARA ONLINE DI FILIPINA - Novilia, Naia Stevani; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
ABSTRACT International Justice Mission (IJM) is a non-governmental organization (NGO) that focuses on addressing exploitation and crimes against children, women, and victims of violence. The Philippines is one of the global epicenters of the problem of Online Sexual Exploitation of Children (OSEC). Every week, more than 20,000 images of child sexual abuse are uploaded to the internet. Therefore, IJM plays a crucial role in tackling the issue of OSEC in the Philippines. Referring to Clive Archer’s theory of international organizations, there are three primary roles that international organizations may assume: as actors, instruments, and arenas. In this study, IJM functions as an actor. As such, IJM fulfills its role by helping establish the Philippines Internet Crimes Against Children Center (PICACC), a coordinated unit that also collaborates with various international and local organizations. IJM also partners with META and provides comprehensive recovery services for OSEC survivors. The research findings show that IJM plays a significant role not only as a legal actor but also as a collaborative partner with national and international institutions. IJM has supported hundreds of rescue operations, contributed to the arrest and conviction of perpetrators, and developed trauma-informed aftercare programs for survivors. This study concludes that IJM’s integrated approach serves as an effective model of intervention in combating OSEC and underscores the importance of crosssector collaboration in addressing online crimes against children. Keyword : International Justice Mission (IJM), Philippines, OSEC, Role